Acute myocardial infarction caused by coronary mucormycotic embolism. (2023) - Kitazawa, Sohei; Kitazawa, Riko
Abstract: Described here is a rare cardiac complication attributed to mucormycosis in a 63-year-old woman who developed sudden cardiac arrest and pulmonary insufficiency in the course of being treated for acute monocytic leukemia (acute myelogenous leukemia, AML M5a). At autopsy, fresh thrombi were noted in the left pulmonary artery and the left atrium. Postmortem coronary angiography revealed complete occlusion of the circumflex branch of the left coronary artery, and histological examination showed a mucormycotic embolism in the corresponding portion. Multiple small mucormycotic thrombi were also noted in both coronary and pulmonary arteries with hemorrhagic infarction in the corresponding areas.